Pengaruh kualitas produk dan penjualan produk terhadap minat beli dengan harga yang dirasakan sebagai variabel moderating pada usaha Ayam Mama - Laura, Netty; Santoso, Rohmat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of product quality and product sales on purchase intention moderated by perceived price. The sample that has been used in this study amounted to 159 respondents from prospective consumers and consumers of Ayam Mama in Jakarta which were obtained from distributing questionnaires using google forms. In this study using Smart PLS 03 software to test the hypothesis to be studied. The results showed that product quality had an effect on buying interest with significant and highest T-Statistics and P Values of the 5 hypotheses tested. Product sales have an effect on buying interest with significant T-Statistics and P Values. This study also shows that the perceived price has an effect on buying interest with a significant T-Statistic and P Value. For the hypothesis of perceived price moderation, it can strengthen the effect of product sales on buying interest, but perceived price moderation weakens the effect of product quality on buying interest.